{Spectra and structure of the 2′-deoxyuridin-1′-yl radical} - Chatgilialoglu, Chryssostomos; Gimisis, Thanasis; Guerra, Maurizio; Ferreri, Carla; Emanuel, Calvin J.; Horner, John H.; Newcomb, Martin; Lucarini, Macro; Franco Pedulli, Gian (Tetrahedron Lett., 1998)
The title C-1' radical, obtained by photolysis of the corresponding tert-butyl ketone in water, was studied spectroscopically by EPR and laser flash photolysis methods and computationally.